2006
DOI: 10.1086/508633
|View full text |Cite
|
Sign up to set email alerts
|

Functional Significance of Shade‐Induced Leaf Senescence in Dense Canopies: An Experimental Test Using Transgenic Tobacco

Abstract: Canopy photosynthesis models have predicted an optimal leaf area index (LAI; leaf area per unit surface area) and leaf nitrogen distribution at which whole-plant carbon gain per unit N is maximized. In this study we experimentally tested these models, using transgenic P SAG12 -IPT tobacco (SAG; Nicotiana tabacum L.) plants with delayed leaf senescence and therefore a greater LAI and more uniform N distribution than the wild type (WT). In a competition experiment, the increased density of surrounding WT plants … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(31 citation statements)
references
References 30 publications
(36 reference statements)
2
27
0
Order By: Relevance
“…The P SAG12 :IPT plants retained their leaves longer than WT plants as expected based upon previous observations (Boonman et al, 2006;Jordi et al, 2000;Gan & Amasino, 1995). The difference between the total number of nodes on the stem, a measure of all the leaves that had ever been produced, and the live leaves present at the time of the harvest is a measure of the number of leaves that had been lost in the canopy due to senescence and abscission ( Table 2).…”
Section: Resultssupporting
confidence: 77%
See 2 more Smart Citations
“…The P SAG12 :IPT plants retained their leaves longer than WT plants as expected based upon previous observations (Boonman et al, 2006;Jordi et al, 2000;Gan & Amasino, 1995). The difference between the total number of nodes on the stem, a measure of all the leaves that had ever been produced, and the live leaves present at the time of the harvest is a measure of the number of leaves that had been lost in the canopy due to senescence and abscission ( Table 2).…”
Section: Resultssupporting
confidence: 77%
“…Assuming that light compensation point changes little with leaf age and/or canopy position, it would appear that the lower leaves on the P SAG12 :IPT stems were a net carbon drain on the plant as a result of self-shading. Boonman et al (2006) made similar observations for P SAG12 :IPT and WT tobacco plants grown at high densities where lower leaves were subject to both intra-canopy and inter-canopy shading. Boonman et al found that growth rates were indistinguishable between the two genotypes at these high planting densities even though the P SAG12 :IPT plants had substantially more photosynthetic tissue than the WT plants.…”
Section: Resultssupporting
confidence: 68%
See 1 more Smart Citation
“…We assume that the affected understorey trees have a relatively low photosynthetic capacity of A * 0 =5 µmol m −2 s −1 with L=1.0 and with k P =0.15. We emphasise that this is only a very rough estimate, designed merely to give an indication of the likely importance of the effect, also noting that it overlooks the importance of leaf production and vertical positioning as well as the dynamics of leaf production in relation to the optimisation of L (Hikosaka, 2003;Boonman et al, 2006).…”
Section: Appendix B Evolutionarily Stable Versus Instantaneous Model mentioning
confidence: 98%
“…Two stem plants had higher productivity of commercial fruits, as well as it proved to be the most effective strategy in the use of water and nutrients. (BOONMAN et al, 2006;XU et al, 1997).…”
Section: Light Supplementation On Tomato Cultivated In Different Manamentioning
confidence: 98%